WEIBULL ANALYSIS OF TWO PARAMETERS IN BAMBOO WASTE AND MECHANICAL PROPERTIES OF STRAIGHT FIBER - Fadilla Rachmanto, Kun
The purpose of this research is to analyze bamboo’s mechanical properties parallel and perpendicular to fiber’s direction. Bamboo was chosen among various kinds of natural composite because it is easy to find, naturally strong, and has affordable price. Apart from its advantages, the usage bamboo as sandwich panel core is still underrated, causing by the lack of knowledge in bamboo’s properties. This research went through a few steps as research method. Firstly, the topic was chosen and literature review was conducted by reading journals and books related with the chosen topic. The next step is the manufacture of the specimen and gives each specimen the treatment needed. Tension test was conducted to each specimen and the data was collected. The data that has been collected is analyzed. Lastly, the conclusion and recommendation were generated based on the findings. This research finds that the outer part of bamboo is stronger than the inner part of it when tension test was conducted. The value obtained reach 177,15 MPa with reliability of 90%. For the test that perpendicular with fiber’s direction, inner part of bamboo is stronger than the outer part. The value obtained reach 5,65 MPa with reliability of 90%. The treatment given tend to makes bamboo’s structure strength decreasing, except for the inner part when pulled parallel to fiber’s direction. This research is limited to Gigantochloa pseudoarundinacea as one of the easiest Bamboo to find in Bandung.